2021
DOI: 10.26451/abc.08.04.07.2021
|View full text |Cite
|
Sign up to set email alerts
|

'Bearly' Changing with the Seasons: Bears of Five Species Show Few Behavioral Changes Across Seasons and at Varying Visitor Densities

Abstract: In natural environments, bear behavior follows seasonal patterns but the zoo environment differs from the natural environment in several ways, including the presence of zoo visitors. Although typically difficult to disentangle, we were able to tease apart the effects of seasonal changes and visitor density on the visibility and behavior of 10 bears representing five species housed at Cleveland Metroparks Zoo due to the disruption caused by COVID-19. We conducted a longitudinal bear behavior monitoring project … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 54 publications
(74 reference statements)
1
12
0
Order By: Relevance
“…The vast majority of her time was devoted to resting despite the season or year, likely due to her age. One other long-term study of the behavioral changes in multiple bear species [13] did not find statistically significant changes in behavior across seasons. However, they did observe changes in locomotion with temperature, which suggests that it is a more sensitive predictor of behavior than prescribed seasons.…”
Section: Changes In Behavior Over Timementioning
confidence: 86%
See 2 more Smart Citations
“…The vast majority of her time was devoted to resting despite the season or year, likely due to her age. One other long-term study of the behavioral changes in multiple bear species [13] did not find statistically significant changes in behavior across seasons. However, they did observe changes in locomotion with temperature, which suggests that it is a more sensitive predictor of behavior than prescribed seasons.…”
Section: Changes In Behavior Over Timementioning
confidence: 86%
“…The degree of exhibit naturalism might also differ across the sites. Seasonal changes in behavior have been documented in other studies of zoo bears [41,42], and seasonal changes in behaviors are well-documented in a number of bear species in the wild (see [7,13] for summaries).…”
Section: Changes In Behavior Over Timementioning
confidence: 99%
See 1 more Smart Citation
“…This ability makes this group important for studies on the impact of the visitor effect on their behavior. The response of bears to the presence of zoo visitors is mixed [16]. For example, visitors can act as both a disturbance factor that increases bears' vigilance and stereotypical behavior, or as a stimulus to encourage normal activity such as exploratory behavior [6,17].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is only one published study on how bears behave during the prolonged absence of visitors, and it was during the global pandemic in 2020. A study at the Cleveland Metroparks Zoo showed that the behavior of five bear species ("sloth bears (n = 3), Andean bears (n = 2), grizzly bears (n = 2), American black bears (n = 2), and a Malayan sun bear (n = 1)", p. 541) did not change during the zoo closure of two months [16]. However, studies that include more individuals of one species and involve several institutions could shed light on general changes in bears' behavior without visitors.…”
Section: Introductionmentioning
confidence: 99%